Revolutionizing X-ray Imaging: Technological Advancements and Their Impact on Patient Care - Assaf Owaidh Alharbi, Ibrahim Dhaifallah Aloufi, Abdurhman Abdulteef Alharbi, Khalid Marzook Alharbi, Sultan Owaid Baraka Al-Sehly; Ibrahim Mupbil Raja Allah Aloufi, Ammar Abdullah Al-Muzaini, Talal Hassan Khulaif Alsaedi, Taher Hassan Khulaif Alsaedi, Saleh Muneer Falah Alsaedi, Saleem Rashed Aljohani, Ahmad Jowaiber Bakheet Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: As Success of Saudi Healthcare System plays an important role in implementing Saudi Arabia’s health strategy, this paper offers a review of publications on the Saudi Healthcare System. The healthcare system of Saudi Arabia needs to be modernized to achieve the targets of Vision 2030 and to meet future challenges of ensuring efficient, effective, and high-quality healthcare for all people in an affordable and accessible manner. The challenges in this respect are many. In the context of the rising demand for quality care due to the increasing population, especially of the elderly, increasing prevalence of chronic diseases, and pandemics, there is immense pressure on the capacities, Workforce, and financial resources. Saudi Arabia is currently passing through a transformational phase.There is a huge demand on the Saudi Healthcare System to provide better healthcare facilities to the rapidly increasing population, as well as the growing elderly population. Saudi Arabia guarantees citizens the right to receive medical care and treatment during emergencies or sickness and aging. Aim of the study: To address an overview of Success of Saudi Health care System in through the opportunities and Challenges a systematic review 2024. Method:Using databases, Pro Quest and Scopus, data extracted from published articles were systematically analyzed for determining the Success of Saudi Healthcare System for improvement and obstacles to achieving higher level. Results: Presents method used for selecting eligible studies for this review. In the first stage, ProQuest and Scopus returned 498 articles. After duplicate articles and those published before 2020 were removed. After excluding studies with sample sizes under 100 and response rates under 60%, 6 articles were included in this review. Conclusion: The Healthcare area in the Kingdom of Saudi Arabia is fundamentally overseen by the Government through the Ministry of Health (MOH) and number of semi Public association who particularly work Saudi Healthcare System. The Success of Saudi Healthcare System in Saudi Arabia varies among the different services. To improve opportunities and Challenges quality, management programmer and organizational culture must be promoted in Saudi Healthcare System. Professional development strategies are also needed for improving the skills and knowledge of healthcare professionals.